AT-TASYBIH WALKINAAYAH BAINA AN-NADZARI WA AT-TATHBIIQI - Hudaili Abdul Hamid Sarmawi (Program Studi Pendidikan Bahasa Arab, 2022)
This research is in the study of the science of rhetoric, as it studies the subject of analogy and metaphor between consideration and application Of detectives talking about them, but did not Taht soft and accurate. This research aims to introduce the reader to the meaning of the Arabic term and its meanings, and to touch the reader himself The breadth of the language of the Holy Qur’an and the Noble Hadith: Knowing the terms of simile and metaphor in them. The research relied on the inductive method in tracking sections and issues, then it was presented with examples with their explanation